2017
DOI: 10.1038/nature23309
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anthrax as a major driver of wildlife mortality in a tropical rainforest

Abstract: Anthrax is a disease of wildlife, livestock and humans predominantly affecting low and 68 middle-income countries 2,4,5 . , suggesting a broad sub-Saharan distribution (Fig. 1) Table S1). 106In TNP we detected Bcbva DNA in 81 carcasses (40%; Fig ( Fig. 2A). We determined Bcbva prevalence within and outside the anthrax invariably led to a clearly reduced survival probability of communities (Fig. 4). 199For example, 76/84 models resulted in extirpation probability higher than 50%, while the 200 model which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
174
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(180 citation statements)
references
References 51 publications
2
174
2
2
Order By: Relevance
“…This study was conducted on flies that associate with wild primates in TNP, Côte d'Ivoire (6°20′–5°10′N, 4°20′–6°50′W). TNP represents the largest remaining primary forest in West Africa and the wild NHP populations present in this ecosystem represent some of the best‐studied in the world; studies on the chimpanzees and monkeys of TNP were initiated in 1979 and 1989 respectively (Boesch & Achermann, ; McGraw, Zuberbühler, & Noë, ) and a veterinary programme that started in 2001 has targeted a broad array of pathogens associated with these populations (Gogarten et al, ; Hoffmann et al, ; Leendertz et al, ; Rich et al, ). We focused on a group of sooty mangabeys habituated to human observers in November 2012 (the Audrenisrou group), which consisted of ~60 individuals during the study period (Gogarten et al, ; Mielke et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted on flies that associate with wild primates in TNP, Côte d'Ivoire (6°20′–5°10′N, 4°20′–6°50′W). TNP represents the largest remaining primary forest in West Africa and the wild NHP populations present in this ecosystem represent some of the best‐studied in the world; studies on the chimpanzees and monkeys of TNP were initiated in 1979 and 1989 respectively (Boesch & Achermann, ; McGraw, Zuberbühler, & Noë, ) and a veterinary programme that started in 2001 has targeted a broad array of pathogens associated with these populations (Gogarten et al, ; Hoffmann et al, ; Leendertz et al, ; Rich et al, ). We focused on a group of sooty mangabeys habituated to human observers in November 2012 (the Audrenisrou group), which consisted of ~60 individuals during the study period (Gogarten et al, ; Mielke et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Sylvatic anthrax, caused by Bc bv a , is a persistent and widespread cause of death in a broad range of mammalian hosts in this ecosystem and was responsible for more than 38% of wildlife mortality observed over 26 years (Hoffmann et al, ; Leendertz et al, ). Bc bv a was the probable cause of death for 11 of 23 mangabeys and 31 of 55 chimpanzees for which necropsies were performed in TNP, and seroprevalence rates are extremely low in these species, suggesting Bc bv a is highly lethal (Hoffmann et al, ; Zimmermann et al, ). Furthermore, Bc bv a DNA was detected in more than 5% of flies sampled throughout TNP and many of these flies were shown to contain viable spores (Hoffmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, wildlife surveillance presents unique challenges associated with limited access to animals, case identification and ecological characteristics of national parks and other forested areas where wildlife inhabit, such as expansiveness of conservation areas [4]. In sub-Saharan Africa, wildlife disease surveillance systems are limited to responding to large outbreaks or narrowly focused retrospective and prospective studies, approaches that have helped in implementing disease outbreak control strategies, estimating specific disease burden and identifying wildlife reservoirs of livestock or human diseases [58]. …”
Section: Introductionmentioning
confidence: 99%
“…Between October 2001 and June 2002, an anthrax outbreak in the tropical forest of Ivory Coast resulted in the death of eight chimpanzees [5]. In fact, a recent comprehensive study of this tropical rain forest found that B. anthracis has been responsible for widespread and persistent mortality among domestic and wild mammals for three decades [8]. Even in developed countries such as Canada, substantial death of wild bison associated with anthrax outbreaks has been reported [9].…”
Section: Introductionmentioning
confidence: 99%